Undergraduate Accounting Curriculum: The Unique Case of Iran - Wijewardena, Hema; Roudaki, Jamal (Accounting Department,, 1997)
After the lslamic Revolution of 1979, the entire education system in Iran was drastically changed to make it more relevant to the lslamic principles. Accordingly, a single undergraduate accounting curriculum designed by the government was imposed on all universities in lran in I982. Since then. undergraduate accounting programmes of all universities have been conducted on the basis ofthis common curriculum. However, there has been criticism that several features of this curriculum are not appropriate in terms of educational objectives and economic conditions ofthe country. This study examined the nature and content of the above curriculum with the purpose of identifying its weaknesses as well as strengths through a survey of perceptions of accounting educators and practitioners in Iran. The ï¬ndings of the study has revealed that despite a few desirable features. the existing undergraduate accounting curriculum in lran suffers from a number ofserious weaknesses.